In‐situ transformation of iron‐bearing minerals in marshland‐derived paddy subsoil. (24th August 2016) - Vogelsang, V.; Fiedler, S.; Jahn, R.; Kaiser, K.
Abstract : Transformations of Fe‐bearing minerals under alternating redox conditions are not fully understood. In‐situ approaches under field conditions have rarely been used. We exposed mesh bags containing ferrihydrite, goethite or nontronite to changing redox conditions in subsoil that had been under paddy management for 100, 700 and 2000 years. After 12 months, the minerals were retrieved and analysed for organic carbon and by X‐ray diffraction; in addition, nontronite was analysed for cation exchange capacity and by Mössbauer spectroscopy at 278 and 4.2 K. Field exposure of the test minerals was complemented by measurements of soil redox potential and analyses of soil water. Minerals accumulated little organic carbon because of high pH and salinity. Goethite samples showed no changes in X‐ray diffraction patterns; therefore, they did not undergo detectable transformation, despite redox potentials frequently around −200 mV. Ferrihydrite transformed into more crystalline oxides, such as lepidocrocite, goethite and haematite. The extent of transformation, presumably by Fe 2+ ‐catalysed recrystallization, increased with the time the soil had been under paddy management. Nontronite samples showed striking changes in surface colour, but no changes in X‐ray diffraction patterns or in cation exchange capacity. However, Mössbauer spectroscopy gave clear indications of irreversible changes within the nontronite crystal structure. Such changes have so far been observed only with chemical reduction, but it seems that they can occur under natural conditions. The results show that the overall redox status of a soil (i.e. the number of redox cycles it has undergone before) governs the extent and direction of mineral transformations during following redox cycles. Highlights: How do ferrihydrite, goethite and nontronite transform under strongly alternating redox conditions? In‐situ exposure of minerals in soil under paddy management for 100, 700 and 2000 years. Fe 2+ ‐catalysed ferrihydrite transformation; irreversible changes in nontronite crystal structure. The number of redox cycles a soil undergoes, governs mineral transformations in later redox cycles.